(untitled) (Journal of the College of Basic Education, 2022)
Science and technology have a major role in our current era, as the progress of countries in all fields is measured by the extent to which they possess the elements of science and technology, and in light of that, the world witnessed rapid scientific and technical developments that included all aspects of life, so that every aspect of it differs from it in the distant and recent past, so the possibility of controlling the outputs and influences of science and technology It is difficult because it depends on the extent to which students can understand the nature of science and technology and their interaction with each other and its impact on society. It is a responsibility that rests with government institutions in general and the educational institution in particular.